Upgrading Students’ Vocabulary through English Movie in Indonesian Context - Ani Fiani; Nur Azizul Fikri; Citra Raflesia (EDULIA: English Education, Linguistic and Art Journal, 2022)
Vocabulary is one of the most important parts of English, so it is important to master as much vocabulary as possible. However, adding to the word is an easy thing to do. Thus, students face challenges in upgrading their vocabulary, so media are needed to upgradestudents’ vocabulary. One of the media that can be used to improve students' vocabulary is English movies. Therefore, this study aims to determine the effectiveness of English movie in upgrading vocabulary. The method used is a library research. The data obtained in this study were taken from several peer-reviewed articles in the last 5 years. The data shows that each student's vocabulary increases by using English movie as a medium. So it can be concluded that English movie are effective in upgrading students' vocabulary, both English movie with subtitles and without subtitles. However, English movie that use subtitles upgrading students' vocabulary more deeply than English movie without subtitles. Keywords: English movie, vocabulary